2018
DOI: 10.1371/journal.ppat.1007066
|View full text |Cite
|
Sign up to set email alerts
|

Histone methylation changes are required for life cycle progression in the human parasite Schistosoma mansoni

Abstract: Epigenetic mechanisms and chromatin structure play an important role in development. Their impact is therefore expected to be strong in parasites with complex life cycles and multiple, strikingly different, developmental stages, i.e. developmental plasticity. Some studies have already described how the chromatin structure, through histone modifications, varies from a developmental stage to another in a few unicellular parasites. While H3K4me3 profiles remain relatively constant, H3K27 trimethylation and bivale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
77
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
3

Relationship

2
8

Authors

Journals

citations
Cited by 56 publications
(78 citation statements)
references
References 63 publications
1
77
0
Order By: Relevance
“…As different intensities of interleukins are detected during schistosomiasis depending on mouse lineage, immunological profile might induce alterations in the signaling pathways of worms allowing adaptation to the host. The presence of different epigenetic marks and changes in the patterns of these marks are involved in the transition of the evolutionary stages of S. mansoni and host-parasite interaction; H3K4me3 and H3K27me3 show greater variation and influence in the transformation of the parasite among phases [14,15]. Epigenator molecules native to intracellular parasites such as protozoa trigger into host new metabolic pathways or interfere inducing initiator host proteins to modify metabolism and promote an environment suitable for parasite reproduction [16].…”
mentioning
confidence: 99%
“…As different intensities of interleukins are detected during schistosomiasis depending on mouse lineage, immunological profile might induce alterations in the signaling pathways of worms allowing adaptation to the host. The presence of different epigenetic marks and changes in the patterns of these marks are involved in the transition of the evolutionary stages of S. mansoni and host-parasite interaction; H3K4me3 and H3K27me3 show greater variation and influence in the transformation of the parasite among phases [14,15]. Epigenator molecules native to intracellular parasites such as protozoa trigger into host new metabolic pathways or interfere inducing initiator host proteins to modify metabolism and promote an environment suitable for parasite reproduction [16].…”
mentioning
confidence: 99%
“…Patterns of specific lysine methyl 106 modifications are achieved by a precise lysine methylation system, consisting of proteins that 107 add, remove and recognize the specific lysine methyl marks. Importantly, histone lysine 108 methylation [14][15][16] and demethylation [17] have been recently demonstrated to be potential 109 drug targets against S. mansoni. 110…”
mentioning
confidence: 99%
“…Studies of the S. mansoni lifecycle have shown that transitions between, and development within, both intermediate and definitive hosts are processes carefully regulated by epigenetic factors [17,18,23,[72][73][74]. While a critical role for histone methylation and demethylation in these processes has been demonstrated [19][20][21]23], the specific contributions of enzymes catalysing these reversible post-translational modifications have not been thoroughly characterised. Following on from our previous investigations demonstrating that anti-neoplastic anthracyclines could bind to the target pocket of SmLSD1 and kill multiple schistosome lifecycle stages [19], we pursued the evaluation of 39 HsLSD1 inhibitors as potentially more potent anti-schistosomals.…”
Section: Discussionmentioning
confidence: 99%